(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In article the order of the circulation of documents in budgetary organizations is exposed to the analysis, the questions connected with reflection of financial operations in documents are considered, recommendations about maintaining financial documentation are made.